Prasasti Huruf Arab Koleksi Museum Masjid Agung Demak - Tawalinuddin Haris (Jurnal Lektur Keagamaan, 2016)
This article discusses an inscription of a historic mosque in Java, namely the Demak Mosque Regol inscription in 1804. The inscription contains information relating to the construction of the mosque Regol by the regents of Demak, KRMT Arya Purbaningrat in 1292 AH (1875 AD). In this inscription it was also mentioned the name of Mas Haji Muhammad Khasan Basri, the qadi or Imam of Demak Mosque. This study concludes that the inscription collection of the Museum of the Great Mosque of Demak is the construction regol or gate Masjid Demak by the Regent of Demak, Kanjeng Raden Mas Tumenggung Arya Prabuningrat, in 1292 H (1875 AD) and the development Tarub Tratag Rambat in 1308 H (1819 AJ) which coincides with 1889 AD, not 1885 as stated on its inscription by the Regent of Demak, Kanjeng Raden Panji Tumenggung Adiningrat. According to the Museum Great Mosque of Demak, the second building (Regol and Tarub Tratag Rambat) was dismantled in 1966. If true, then the demolition of the building took place during the reign of the Regent of Demak Raden Indriyo Yatmo Pranoto (1958-1966). From the reading of inscriptions that the year 1804 was not found. The year (1804) was obtained if the number 1292 H is converted to Java year system, so the numbers refer to the year 1804 Javanese year (1804 AJ). In other words, the numbers associated with the 1804 inscription naming Regol Masjid was never mentioned in the inscriptions, so the inscription naming here is less relevant. Keywords: Mosque, Inscription, Demak, Java, Museum, History. Artikel ini membahas sebuah inskripsi Mesjid bersejarah di Jawa, yakni Inskripsi Regol Masjid Demak tahun 1804. Inskripsi tersebut memuat informasi berkenaan dengan pembangunan Regol Masjid oleh bupati Demak, yaitu KRMT Arya Purbaningrat pada tahun 1292 H (1875 M). Dalam inskripsi ini disebut juga nama Mas Haji Muhammad Khasan Bashri, qadi atau imam Masjid Demak. Studi ini berkesimpulan bahwa isi prasasti koleksi Museum Masjid Agung Demak adalah tentang pembangunan regol atau pintu gerbang Masjid Demak oleh Bupati Demak, Kanjeng Raden Mas Tumenggung Arya Prabuningrat, pada tahun 1292 H (1875 M) dan pembangunan Tarub Tratag Rambat pada tahun 1308 H (1819 AJ) yang bertepatan tahun 1889 M, bukan tahun 1885 M seperti tertera pada prasastinya oleh Bupati Demak, Kanjeng Raden Tumenggung Panji Adiningrat. Menurut catatan Museum Masjid Agung Demak, kedua bangunan itu (Regol dan Tarub Tratag Rambat) dibongkar pada tahun 1966. Jika benar, maka pembongkaran bangunan itu berlangsung pada masa pemerintahan Bupati Demak Raden Indriyo Yatmo Pranoto (1958 1966). Dari hasil pembacaan inskripsi juga tidak ditemukan angka tahun 1804 dalam prasastinya. Angka tersebut (tahun 1804) diperoleh jika angka tahun 1292 H dikonversikan ke tahun Jawa, sehingga angka 1804 mengacu kepada tahun Jawa (1804 AJ). Dengan kata lain, angka 1804 yang dikaitkan dengan penamaan Prasasti Re gol Masjid tidak pernah disebut dalam prasastinya, sehingga penamaan prasasti tersebut menurut hemat penulis kurang relevan. Kata Kunci: Masjid, Prasasti, Inskripsi, Demak, Jawa, Museum, Sejarah.